The Right to a Fair Trial: the ECtHR Case-Law and Its Implementation in the Ukrainian Judiciary - Denysova, Alina V.; Blaga, Alla B.; Makovii, Viktor P.; Kaliuzhna, Yevheniia S. (PRAWO i WIĘŹ, 2022)
Since the Ukrainian jurisprudence needs new legal mechanisms based on the implementation of the decisions of the European Court of Human Rights (hereinafter – EctHR) that will ensure the exercise of the right to a fair trial, the subject under the study is relevant. Authors of this study aim to examine the right to a fair trial in terms of its content and provision in Ukraine through the prism of decisions of Ukrainian courts in various instances and the relevant case-law of the EctHR. The conducted research involves studying empirical and theoretical materials related to the content of normative consolidation and law enforcement use of the right to a fair trial. The methodological framework also includes the following research techniques and methods: dialectic, systemic, functional and structural, analysis, and synthesis. The authors determine the said right is considered within its constituent elements and relevant manifestations in legal science and case-law, including fairness and publicity of the trial, compliance with the signs of independence, impartiality, legality, and the rule of law, equality of participants, and proceedings within reasonable time limits. The characteristics of the said right and the mentioned elements are subjected to appropriate interpretation within the relevant judgments of the ECtHR during proceeding case materials in national courts of the signatory states to the Convention. There is an extensive terminological and procedural experience of the ECrHR used in the case-law of Ukraine in matters of ensuring the right to a fair trial and its exercise. The conclusions of the article may be used to improve legislative, law enforcement practice, and research in the framework of creating legal structures to ensure the exercise of the said right in the country, taking into account the ECtHR case-law.